Nasionalisme Di Puncak Gunung: Etnografi Komunitas Pemuda Pecinta Alam dalam Wacana Ecosophy dan Gerakan Lingkungan di Malang - Fuji Riang Prastowo; A Harun Al Rasyid (Jurnal Studi Pemuda, 2019)
The Nature Lovers community, in Indonesia, have a unique habit of celebrating the conquest of the mountain peak by singing a National anthem of Indonesia Raya along with the raising of nation flag. Interestingly, many of them have a dream to attend a flag-raising ceremony in order to celebrate the independence day of the Republic of Indonesia on 17 August at the top of the mountain. By using the 'phenomenology-based ethnography' method among the Nature Lovers community in Malang, this study seeks to answer about how these young people construct a discourse on environmental movements in their climbing activities and how they construct nationalism through their climbing rites. Analysis of the study used the concepts of Ecosophy from Arne Naess and Nationalism from Benedict Anderson. Through these two conceptual frames, the results of the study show that there is a close connection between mountain climbing and ecosophy discourse with nationalism, both of which have similar philosophical values in search of the self through natures.  Climbing is the effort of young people to get closer to nature and the process of finding themselves through the conquest of the ego during the journey to further strengthen the value of ecosophy or individual connection to nature. While patriotic celebrations at the top of the mountain are manifestations of nationalism rooted in the 'deep ecology movement' which is constructed by the 'imagined community' based on the solidarity of the climbers who have the same souls in nature. It can be said that the connection between ecosophy and nationalism is represented by the romanticism of the mountain climbing.